Notas sobre la ecología de una población relicto de la lagartija de las Lomas Microlophus tigris (Tropiduridae: Sauria)en el Parque Zoológico Las Leyendas (Lima, Perú) - Jordán Arizmendi, Juan Carlos (2011)
I studied activity patterns, microhabitat use and thermal ecology of a small-wild population of the Loma’s lizard, Microlophus tigris in Parque Las Leyendas Zoo, from April to October of 2006. Microlophus tigris individuals were active in a variety of microhabitats, from bushes and vegetation debris to prehispanic bricks (adobes) and litter, during the hottest hour of the day. Mean body temperature (29,4 ºC) was similar to body temperature observed in a natural population from Lomas de Lachay, although in Parque de Las Leyendas, substrate temperature was higher than air temperature, probably related to thermal properties of materials used as microhabitats and to seasonal differences. We encouraged the Zoo to takes conservation measures to protect this endangered wild population of lizard in Lima city.